Voriconazole incorporated nanofiber formulations for topical application: preparation, characterization and antifungal activity studies against Candida species - Esenturk, Imren; Balkan, Timucin; Ozhan, Guel; Doesler, Sibel; Gungor, Sevgi; Erdal, M. Sedef; Sarac, Abdulkadir Sezai (Informa UK Limited, 2020)
In this study, voriconazole (VCZ) incorporated polyvinyl alcohol/sodium alginate electrospun nanofibers were produced and, then crosslinked with glutaraldehyde for topical antifungal treatment. The nanofibers were characterized in terms of fiber size, surface morphology, and compatibility between drug-polymer and polymer-polymer using scanning electron microscopy, atomic force microscopy, attenuated total reflection-Fourier transform infrared spectroscopy, and high pressure liquid chromatography. After optimization studies, in vitro drug release, skin penetration, and deposition studies were performed using Franz diffusion cells. Antifungal activities of the nanofiber formulations against Candida albicans, Candida tropicalis, and Candida parapysilosis strains were evaluated using susceptibility test and subsequently time-kill study was performed against C. albicans. The cytotoxicity study was performed using 4-succinate dehydrogenase viability assay on mouse fibroblast cell line. The release rate of VCZ from crosslinked nanofibers was slower than that of non-crosslinked nanofibers and Higuchi kinetic model best fitted to the in vitro release data of both of formulations. VCZ deposited in deeper skin layers from nanofiber formulations was higher than that of the control formulation (VCZ solution in propylene glycol (1% (w/v)). According to the susceptibility and time-kill studies, all of the nanofiber formulations showed antifungal activity against C. albicans with confirming no cytotoxicity on mouse fibroblast cells.
Keywords: Antifungal Agents; Alginates; Swine; Administration, Topical; Skin Absorption; Candidiasis; Nanofibers; Cell Line; Drug Liberation; Mice; Drug Delivery Systems; Polyvinyl Alcohol; Animals; Humans; Voriconazole; Candida